Sistem Pendukung Keputusan Pemberian Kredit Sepeda Motor Pada PT Adira Finance Medan Menggunakan Metode SAW - Mikhael Armando Manullang; Hasanul Fahmi (Jurnal Nasional Komputasi dan Teknologi Informasi (JNKTI), 2021)
Many people who want to own a motorbike, but do not have sufficient funds to buy a motorbike in cash, require a way to own a motorbike using a credit payment system. The formulation of the problem to be resolved in this study is how to design the SPK in determining motorcycle loans for new customers at PT Adira Finance using the SAW method. The limitation of the problem in this research is that the application does not handle the investment of funds from customers in the form of savings, time deposits and others, the application only supports the decision to grant credit to customers with predetermined criteria and the application does not handle the addition of customer criteria. The research objective is PT. Adira Finance can determine creditworthy debtors and prepare SPK to determine creditworthiness at PT. Adira Finance. From the results of the calculation of the V value above, a ranking is made: V1 = Customer 1 (0.91) V4 = Customer 4 (0.91) V2 = Customer 2 (0.63) V3 = Customer 3 (0.51) V5 = Customer 5 (0.31).